Penyuluhan Kesehatan tentang Personal Hygiene : Sikat Gigi dan Cuci Tangan yang Benar di SD Negeri 200501 Salambue - Pane, Mustika Dewi (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2022)
Personal Hygiene is a cleaning activity carried out by someone as an effort to maintain health and prevent a disease. The application of personal hygiene aims to prevent the spread of germs obtained from the surrounding environment. Personal hygiene should be started from an early age. This is because children are vulnerable to health problems related to the application of personal hygiene in everyday life. It is hoped that this activity will allow children to get information related to personal hygiene and apply it in everyday life to prevent infectious diseases that can be prevented by personal hygiene. The activity was carried out for elementary school children with the hope that children would develop the habit of washing their hands and brushing their teeth from an early age. This activity was carried out for grade 1 elementary school children, with a total of 24 children. The series of activities was filled with presentation of material related to hand washing and toothbrushing, then demonstrations of how to wash hands and brush teeth properly. The results after this activity were seen that elementary school children understood the material that had been given about hand washing and toothbrushing, and how to properly wash hands and brush teeth. During the re-demonstration session there were two children who washed their hands well but with a little help. It is hoped that for the next step, the school will emphasize more regarding personal hygiene habits at school, and continue to provide health-related information to families and the school environment